Male-origin microchimerism and endometrial cancer: A prospective case-cohort study. (August 2022) - Hallum, Sara; Petersen, Gitte Lindved; Jakobsen, Marianne Antonious; Pinborg, Anja; Kuhlmann, Caroline; Tjønneland, Anne; Kamper-Jørgensen, Mads
Abstract: Background: Many women carry male cells of presumed fetal origin–so-called male-origin microchimerism (MOM)–in their circulation and tissues. Studies have found reduced risks of hormone dependent cancers, including breast and ovarian cancer, among MOM-positive women. The aim of this study was to investigate the association between MOM and endometrial cancer. Methods: We designed a prospective case-cohort study including 76 cases and 505 controls from the Diet, Cancer and Health cohort aged 50–64 years and cancer-free at enrolment in 1993–1997. We analyzed blood samples for the presence of Y-chromosome ( DYS14) . We examined the association between MOM and endometrial cancer in weighted Cox regression models. As a negative control outcome, we studied the association between MOM and injuries to test for spurious associations. Results: We detected MOM in 65.9% controls and 54.0% cases. While we observed no overall association between MOM and endometrial cancer (HR=0.73, 95% CI: 0.47–1.15), we found a borderline significantly reduced rate of Type 1 endometrial cancer (HR=0.66, 95% CI: 0.39–1.00), but not other types of endometrial cancers (HR=1.00, 95% CI: 0.35–2.90). The reduced rate was not modified by hormonal exposure (P = 0.79). We found no association between MOM and risk of injuries (HR=0.96, 95% CI: 95% CI: 0.78–1.21). Conclusions: Our study suggests that MOM is inversely associated with Type 1 endometrial cancer, without evidence of an interaction with hormonal exposure. We encourage future research to confirm our findings. Highlights: Many women carry male cells in their circulation or tissues – a phenomenon termed male-origin microchimerism (MOM). MOM is associated with some hormone-dependent cancers; whether the reduced risk extends to endometrial cancer is unknown. We found that MOM was inversely associated with Type 1 but not other types of endometrial cancer. The reduced risk of endometrial cancer did not depend on measures of hormonal exposure. Our study suggests that MOM may provide novel insights into endometrial cancer etiology.